2016
DOI: 10.15414/afz.2016.19.si.111-113
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of a SOD1 missense mutation in Czechoslovakian Wolfdog

Abstract: Canine degenerative myelopathy occurs in many dog breeds, mainly German Shepherd dogs. The causative mutation E40K in the SOD1 gene changes the structure and function of the superoxide dismutase 1 protein. The genetic makeup of the Czechoslovakian Wolfdog breed, that resulted from hybridization between Carpathian wolves and German Shepherds in the 1950s, shows a higher proportion of the dog than wolf genetic background. In the present study we have screened the Czechoslovakian Wolfdog population for the causat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The heterozygosity and homozygosity rates observed were similar to those previously recorded in the same breed (0.25 vs. 0–0.17 and 0.04 vs. 0–0.06 for heterozygosity and homozygosity, respectively) [ 9 , 18 - 20 ] and other breeds (Airedale Terrier, American Hairless Terrier, Beagle, Belgian Sheepdog, Borzoi, Boxer, Boykin, Chow Chow, Spaniel, and Kuvasz) ( Table-2 ) [ 6 - 9 , 18 - 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…The heterozygosity and homozygosity rates observed were similar to those previously recorded in the same breed (0.25 vs. 0–0.17 and 0.04 vs. 0–0.06 for heterozygosity and homozygosity, respectively) [ 9 , 18 - 20 ] and other breeds (Airedale Terrier, American Hairless Terrier, Beagle, Belgian Sheepdog, Borzoi, Boxer, Boykin, Chow Chow, Spaniel, and Kuvasz) ( Table-2 ) [ 6 - 9 , 18 - 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…As stated in Table S1 , Zeng et al [ 22 ] identified the mutant allele frequency as 0.3400. Another study conducted in Slovakia on 54 Czechoslovakian Wolfdogs showed an allele frequency of 0.2500 [ 25 ]. This relatively high mutant allele frequency may be attributed to the relatedness of the Czechoslovakian Wolfdog to the German Shepherd.…”
Section: Discussionmentioning
confidence: 99%